(untitled) (Sociologisk Forskning, 2017)
Sweden has experienced a sharp increase in migration flows in the last decades. Projections estimate that the migrant population rate will continue to grow in the near future. Given the centrality of health for the successful engagement of individuals in society, health aspects of migration have emerged as an important area of study. In this research note, we present a brief overview of current knowledge and argue in favour of developing a social determinants perspective on health in future research.